Towards greater integration: Prospects for the development of agri-food trade between the EU and RCEP countries - Joanna Łukasiewicz; Bartłomiej Bajan; Karolina Pawlak (PLoS ONE, 2025)
The Regional Comprehensive Economic Partnership (RCEP) is the largest free trade agreement in the world, making it a potentially attractive trading partner for the European Union (EU). This paper aims to fill a research gap by examining agri-food trade between the EU and RCEP, with a focus on uncovering opportunities for sectoral cooperation and identifying competitive dynamics. It employs trade structure similarity and intra-industry trade analysis, including horizontal and vertical trade flows. Using the Export Similarity Index (ESI) and Product Similarity Index (PSI), the findings indicate stable, moderate competition in agri-food trade between the EU and RCEP, with similarity indices ranging from 0.32 to 0.35. While intra-industry trade remains limited due to geographic distance, there is notable potential for expanding high-quality EU agri-food exports. The results suggest that targeted trade policies could enhance cooperation by leveraging the EU’s export strengths to meet RCEP demand. The study provides a strategic framework for future negotiations, emphasizing sectoral approaches to optimize trade outcomes and maximize trade benefits between the EU and RCEP countries.